A Green Preconcentration Method for Determination of Cobalt and Lead in Fresh Surface and Waste Water Samples Prior to Flame Atomic Absorption Spectrometry. (22nd November 2012) - Naeemullah,; Kazi, Tasneem Gul; Shah, Faheem; Afridi, Hassan Imran; Khan, Sumaira; Arian, Sadaf Sadia; Brahman, Kapil Dev
Abstract : Cloud point extraction (CPE) has been used for the preconcentration and simultaneous determination of cobalt (Co) and lead (Pb) in fresh and wastewater samples. The extraction of analytes from aqueous samples was performed in the presence of 8-hydroxyquinoline (oxine) as a chelating agent and Triton X-114 as a nonionic surfactant. Experiments were conducted to assess the effect of different chemical variables such as pH, amounts of reagents (oxine and Triton X-114), temperature, incubation time, and sample volume. After phase separation, based on the cloud point, the surfactant-rich phase was diluted with acidic ethanol prior to its analysis by the flame atomic absorption spectrometry (FAAS). The enhancement factors 70 and 50 with detection limits of 0.26 μ g L −1 and 0.44 μ g L −1 were obtained for Co and Pb, respectively. In order to validate the developed method, a certified reference material (SRM 1643e) was analyzed and the determined values obtained were in a good agreement with the certified values. The proposed method was applied successfully to the determination of Co and Pb in a fresh surface and waste water sample.